Taxonomic Hierarchy and Evolutionary Scenario of the Genus Group Apodemus s. l. (Muridae) of the Palearctic based of Genetic Differentiation in the cyt-b Gene - Mezhzherin , S.; Tereshchenko, V. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2022)
Characters of taxonomy and evolutionary scenario based on genetic differentiation of generic groups of forest and field mice Apodemus s. l. were established by analyzing the variability of the cyt-b (cytochrome-1, cytb) gene. For this purpose, 124 sequences of Apodemus s. l. and other Palearctic Muridae genera (Mus, Micromys, Rattus) were downloaded from GenBank. The adequacy of the categories of semispecies, allospecies, species, whose genetic differentiation corresponds to GD ranges of 0.03–0.06, 0.06–0.1 and 0.1–0.15, has been proven. Within the genus Sylvaemus the following species are recognised: S. (Sylvaemus) alpicola, S. (S.) arianus (= witherbyi), S. (S.) flavicollis, S. (S.) hyrcanicus, S. (S.) ponticus, S. (S.) (superspecies) sylvaticus, S. (S.) (superspecies) uralensis, S. (Karstomys) epimelas, S. (K.) mystacinus, S. (?) rusiges: within Apodemus: A. agrarius, A. chevrieri, within Alsomys: Al. argenteus, Al. ilex, Al. latronum, Al. (superspecies) major (= peninsulae), Al. nigrus, Al. semotus, Al. speciosus. Generic taxonomy remains ambiguous, which is caused not only by different scales of differentiation of most species of Western and Eastern Palaearctic lineages, but also by the lack of information on key genus-specific characters: the number of roots on upper molars and number of mammary glands for most East Asian species.